MATERIALNA OCHRONA KONSUMENTA - Lemkowski, Marcin (Wydział Prawa i Administracji UAM, 2002)
The article is an attempted discussion of some regulations introduced into the Polish Civil Code with the Act of 2nd March 2000 on consumer protection and accountability for a dangerous product. This regulation sets out the framework of consumer protection in the Polish law by means of two types of provisions. The provisions of the first type regulate consumer contract: its conclusion, form and amendments, as well as any additional obligations of the parties involved in the process of shaping the legal relation. In no way do they, however, refer to the content of the contract itself; instead, they create formal consumer protection. On the other hand, the other group of regulations allows an interference with the content of the civil law relation, and it therefore provides material consumer protection. The author discusses both groups of the regulations, analysing the extent o f their modification and their effect on the Polish goods market.
MATERIAL CONSUMER PROTECTION